2011
DOI: 10.1166/jnn.2011.3434
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Silver Bimetallic System on Natural Clinoptilolite: Thermal Reduction of Cu2+ and Ag+ Exchanged

Abstract: Copper-silver bimetallic system supported on natural clinoptilolite from Tasajeras deposit (Cuba) was studied. Bimetallic samples were prepared by simultaneous ion exchange, and reduced in a wide temperature range in a hydrogen flow. The main goal of the work was analysis of the mutual influence of both metals on their reduction process and the properties of the resultant particles. Analysis was done by combined use of XRD and UV-Vis spectroscopy. The reduction of Cu2+ and Ag+ cations shows existence of notabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 0 publications
5
31
0
Order By: Relevance
“…Because of this, natural zeolites offer a wide range of applications, and one of the most notable is the removal of contaminant ions in water and soil [3][4][5]. It is reported that natural zeolites, specifically clinoptilolite, have been used in the removal of Mn, Cu, Ar, Pd, Cd, and Zn [4][5][6]. However, it is important to study the rate of adsorption of these species, in order to provide the optimum conditions for the adsorption process.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, natural zeolites offer a wide range of applications, and one of the most notable is the removal of contaminant ions in water and soil [3][4][5]. It is reported that natural zeolites, specifically clinoptilolite, have been used in the removal of Mn, Cu, Ar, Pd, Cd, and Zn [4][5][6]. However, it is important to study the rate of adsorption of these species, in order to provide the optimum conditions for the adsorption process.…”
Section: Introductionmentioning
confidence: 99%
“…The diffraction pattern also shows peak related to impurity phases (quartz and clinoptinolite), as labeled in Figure 3. A small change in the intensity of the peaks is observed on Fe 2+ ZP and Fe 3+ ZP, as is often observed after ion exchange as a consequence of changes in the location and concentration of extra-framework cations in the zeolite channels [27,28]. This suggests that the crystalline structure of mordenite was not altered by the treatment with acid solutions, and that the zeolite is stable under applied conditions.…”
Section: Xrd Analysismentioning
confidence: 68%
“…The spectrum of Ag-clinoptilolite shows a peak at 303 nm, in agreement with previous studies. The UV-Vis DRS spectra of zeolitic-rich tuffs containing primarily clinoptilolite and its silver-modified forms are used to determine the states of silver in the extra-framework sites (Concepción-Rosabal et al , 2005; Rodríguez-Iznaga et al , 2011; Chmielewská et al , 2014; Suligoj et al , 2020). After the DBD-like plasma jet application, new absorption peaks centred at 325 and 370 nm appeared.…”
Section: Resultsmentioning
confidence: 99%